2022
DOI: 10.1371/journal.pone.0258837
|View full text |Cite
|
Sign up to set email alerts
|

Impaired trigeminal control of ingestive behavior in the Prrxl1-/- mouse is associated with a lemniscal-biased orosensory deafferentation

Abstract: Although peripheral deafferentation studies have demonstrated a critical role for trigeminal afference in modulating the orosensorimotor control of eating and drinking, the central trigeminal pathways mediating that control, as well as the timescale of control, remain to be elucidated. In rodents, three ascending somatosensory pathways process and relay orofacial mechanosensory input: the lemniscal, paralemniscal, and extralemniscal. Two of these pathways (the lemniscal and extralemniscal) exhibit highly struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that ingestive behaviour involved a continuous flow of somatosensory input from the oral region, which is used to guide oral grasping (Zeigler, Jacquin, & Miller, 1984). Orosensory deafferentation induces persistent hypophagia and a reduction in body weight, whereas whisker deafferentation appears to make little or no contribution to food intake and body weight regulation (Resulaj et al, 2022; Zeigler, Semba, et al, 1984). Although the experimental context was different, some of our findings were comparable, as initial snout contact with the nose tip and the contact phase duration lengthened after injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ingestive behaviour involved a continuous flow of somatosensory input from the oral region, which is used to guide oral grasping (Zeigler, Jacquin, & Miller, 1984). Orosensory deafferentation induces persistent hypophagia and a reduction in body weight, whereas whisker deafferentation appears to make little or no contribution to food intake and body weight regulation (Resulaj et al, 2022; Zeigler, Semba, et al, 1984). Although the experimental context was different, some of our findings were comparable, as initial snout contact with the nose tip and the contact phase duration lengthened after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation and lesion experiments have shown that trigeminal orosensory inputs provide an essential link in the stimulus–response chain mediating eating in the rat (Resulaj et al, 2022; Zeigler, Jacquin, & Miller, 1984). Trigeminal orosensory deafferentation in the rat decreases responsiveness to food and water, disrupting sensorimotor control of eating and drinking.…”
Section: Introductionmentioning
confidence: 99%